(3cJGH aj Gdabg GdeGdcjs - (3eLghds ((3YKeGf Hf GdaGge YHO GdQMefs)
(3ChdgG (B:s
(3HYO GdHSedI ; CYde Cfg JLGPH GdMVGfI CeQGf CMOgeG GdfcGM dCfg efTCgG hGdBNQ GdHjY dCf GdMGVf Ydi MaX GdeMVhf hdg bHV fabJg hJMUjd eG Hg bhGeg HGdfabIs
(3BNQgG (B:s
(3hYdjg aGdeGQGO HGdLhGR GdEPf ajTed GdhGLH Ch jbGd GdhGLH RLQg HeG gh CYe ef GdVQH hCeG GdVQH HNUhUg aMceg GdLhGR dCf CeQg TOjO hLGR Cj CPf ddCejQ Ch GdNdjaI YRdg Cj GdbGVjs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3Gdabg GdeGdcjs